Перспективи розвитку управлінського обліку на вітчизняних підприємствах - Безверхня, Юлія Вікторівна; Безверхняя, Юлия Викторовна; Bezverkhnya, Yuliia (My University, 2019)
UK: Розглянуто стратегічні цілі впровадження управлінського обліку на вітчизняних підприємствах. Проаналізовано стратегію підприємств на сучасному ринку, яка забезпечує зв'язок їхніх фінансових результатів і ринкових позицій у конкурентному середовищі. Висвітлено окремі аспекти формування збалансованої системи показників діяльності та розроблення організаційної структури підприємств. Обґрунтовано необхідність створення системи управлінського обліку за центрами фінансової відповідальності для підвищення ефективності прийняття управлінських рішень. Визначено перспективні напрями розвитку вітчизняного управлінського обліку з урахуванням іноземного досвіду та його подальшої адаптації до міжнародних стандартів. RU: Рассмотрены стратегические цели внедрения управленческого учета на отечественных предприятиях. Проанализирована стратегия предприятий на современном рынке, которая обеспечивает связь их финансовых результатов и рыночных позиций в конкурентной среде. Освещены отдельные аспекты формирования сбалансированной системы показателей деятельности и разработки организационной структуры предприятий. Обоснована необходимость создания системы управленческого учета по центрам финансовой ответственности для повышения эффективности принятия управленческих решений. Определены перспективные направления развития отечественного управленческого учета с учетом иностранного опыта и его дальнейшей адаптации к международным стандартам. EN: The purpose of the article is to consider the strategic objectives of the introduction of management accounting in domestic enterprises, the rationale for its need in modern conditions and prospects for further development. The world economy is rapidly moving towards globalization of all processes. To be competitive in the domestic and foreign markets, modern enterprises need a flexible, quickly adaptable management system. For this purpose, the enterprises develop a longterm strategy and introduce a system of management accounting. The relevance of the study is that management accounting needs to be developed and improved within the framework of global management trends. And cost management of the enterprise directly affects the formation of financial results. It is also necessary to take into account foreign experience in the application of management accounting models and synchronize it with international standards, while taking into account national peculiarities of doing business. This study discusses the strategic objectives of the introduction of management accounting in domestic enterprises. The strategy of the enterprises in the modern market which provides connection of their financial results and market positions in the competitive environment is analyzed. Some aspects of the formation of a balanced system of performance indicators and the development of the organizational structure of enterprises are highlighted. The necessity of creation of system of management accounting on the centers of financial responsibility with the purpose of increase of efficiency of managerial decision-making is proved. The perspective directions of development of the domestic management accounting taking into account foreign experience and its further adaptation to the international standards are defined.
Prospects of development of management accounting in domestic enterprises
Keywords: управлінський облік; стратегія; структура; управлінські рішення; центри відповідальності; міжнародні стандарти; управленческий учет; стратегия; управленческие решения; центры ответственности; международные стандарты; management accounting; strategy; structure; management decisions; responsibility centers; international standards